If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -8 = 35 Reorder the terms: -8 + x = 35 Solving -8 + x = 35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + x = 35 + 8 Combine like terms: -8 + 8 = 0 0 + x = 35 + 8 x = 35 + 8 Combine like terms: 35 + 8 = 43 x = 43 Simplifying x = 43
| .33(6x-9)=-1.5(4x-5) | | d^3-24d=-2d^2 | | 20+7m=5+10m | | d^3-24d=-2d^2 | | .33(6x-9)=-1.5(4x-5) | | d^3-24d=-2d^2 | | 7[6-y]=-3[y-2] | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | 50+.25x=20+.40x | | -L=-8 | | -L=-8 |